2023
DOI: 10.1021/acs.est.3c04578
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Mechanistic Study of Transgenerational Neurotoxicity in Zebrafish upon Life Cycle Exposure to Decabromodiphenyl Ethane (DBDPE)

Yumiao Sun,
Xiaochen Wang,
Shanqi Zhou
et al.

Abstract: The novel brominated flame retardant decabromodiphenyl ethane (DBDPE) has become a ubiquitous emerging pollutant in the environment, which may evoke imperceptible effects in humans or wild animals. Hence in this study, zebrafish embryos were exposed to DBDPE (0, 0.1, 1, and 10 nM) until sexual maturity (F0), and F1 and F2 generations were cultured without further exposure to study the multi-and transgenerational toxicity and underlying mechanism. The growth showed sexdifferent changing profiles across three ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Notably, in terms of neurotoxicity, several environmental contaminants, such as polychlorinated biphenyls and bisphenol A, have been found to exert greater toxicity in males than females. These sex-specific effects are presumed to be attributed to the inherent substantial differences in sex hormonal levels and detoxifying capacities between males and females . Previous studies have demonstrated that diazinon exposure had a more pronounced effect on perturbing the gut microbiome in male mice, thereby inducing more severe neurotoxicity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in terms of neurotoxicity, several environmental contaminants, such as polychlorinated biphenyls and bisphenol A, have been found to exert greater toxicity in males than females. These sex-specific effects are presumed to be attributed to the inherent substantial differences in sex hormonal levels and detoxifying capacities between males and females . Previous studies have demonstrated that diazinon exposure had a more pronounced effect on perturbing the gut microbiome in male mice, thereby inducing more severe neurotoxicity .…”
Section: Discussionmentioning
confidence: 99%
“…Adult zebrafish exposed for 21 days were tested between the morning and afternoon period (10:00 to 16:00). The shoaling behavior assay was conducted with three fish (forming one shoal) in each test tank (10.4 cm height ×23 cm length ×10.4 cm width), following established protocols . After a 5 min adaptation period, we recorded 10 min of video using the Video-Track system (View Point Life Sciences, Inc., Lyon, France).…”
Section: Methodsmentioning
confidence: 99%